Nonlinear approximation for perturbations in ΛCDM - Rigopoulos, Gerasimos; Valkenburg, Wessel (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
We describe inhomogeneities in a ΛCDM universe with a gradient series expansion and show that it describes the gravitational evolution far into the nonlinear regime and beyond the capacity of standard perturbation theory at any order. We compare the gradient expansion with exact inhomogeneous ΛLTB solutions (Lemaître-Tolman-Bondi metric with the inclusion of a cosmological constant) describing growing structure in a ΛCDM universe and find that the expansion approximates the exact solution well, following the collapse of an over-density all the way into a singularity.
Published 17 August 2012
Gesehen am 26.06.2018